A Study on the Diazo-Transfer Reaction Using o-Nitrobenzenesulfonyl Azide - Gwak, Sungduk; Lee, Ji Hye; Kwon, Hyeok-Jun; Han, Hogyu (Synlett, 2023)
15N-Labeled azides have a great potential as practical and effective tags for vibrational probing and hyperpolarized magnetic resonance imaging of biomolecules. They can be synthesized by reaction of primary amines with a 15N-labeled diazo-transfer reagent. TfNN15N, a γ-15N-labeled diazo-transfer reagent, was developed to prepare β-15N-labeled azides; these are vibrational probes devoid of strong spectral interference by Fermi resonance. To overcome the stability and safety problems associated with TfNN15N, there is a strong demand for the development of a novel γ-15N-labeled diazo-transfer reagent. We present a study on the diazo-transfer reaction using o-nitrobenzenesulfonyl azide (o-NsN3). o-NsNN15N, a γ-15N-labeled diazo-transfer reagent, was newly developed and found to be better than TfNN15N with respect to its physicochemical properties and ease of synthesis. Unlike TfNN15N, however, o-NsNN15N was found to afford a mixture of β- and γ-15N-labeled azides rather than the β-15N-labeled azide alone. A mechanism for the diazo-transfer reaction of o-NsNN15N with primary amines is proposed to explain the formation of such isotopomeric mixtures.
Keywords: diazo-transfer reagents; sulfonyl azides; nosyl azide; organic azides; 15N labeling; isotopomerism